Exploring Social Media Marketing for Promoting Tourism Villages: A Qualitative Approach - Fathor AS; Sanaji; Yessy Artanti; Rosa Prafitri Juniarti (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Tourism villages, such as those in Bangkalan Regency, hold significant potential to boost local economies, but their success depends on effective promotional strategies. This study aims to examine the use of social media marketing as a promotional tool for developing tourism villages, focusing on Tlangoh Beach Tourism Village. A descriptive qualitative approach was employed, using field observations, in-depth interviews with one manager and four visitors, and documentation of social media content. The findings reveal that the tourism village uses Facebook and Instagram for promotion, but the efforts are suboptimal due to infrequent posts, limited engagement, and reliance on word-of-mouth as the primary information source for visitors. Financial constraints and a lack of skilled personnel further hinder effective marketing. To improve, managers should enhance content quality, increase posting frequency, and establish partnerships with travel agencies or local institutions. This study concludes that social media marketing can significantly enhance tourism village promotion if implemented consistently and strategically. It contributes to understanding how resource-constrained destinations can leverage digital platforms and offers practical insights for managers to increase visitor numbers through targeted, cost-effective strategies.